Influência da pandemia de COVID-19 na dor crônica e estratégias de desenvolvimento de telerreabilitação - Pereira, Thaís Alves Barreto (2023)
Introduction: Patients with chronic pain, such as fibromyalgia (FM), commonly experience significant psychosocial, emotional, and physical changes and may be more affected during periods of crisis, such as the recent COVID-19 pandemic, due to the social distancing measures implemented to contain the novel coronavirus (SAR-CoV-2). Moreover, the need for ongoing healthcare treatments during periods of contact restrictions has led to the utilization of tele- rehabilitation programs, which will continue to be implemented beyond the pandemic period. However, this resource may trigger beliefs and expectations in FM patients that can lead to poor adaptation and treatment abandonment. Therefore, it is crucial to understand the acceptability of tele-rehabilitation treatments among these patients to develop strategies for clinical management. Objectives: To assess pain characteristics, psychoemotional symptoms, sleep quality, and level of physical activity in patients with chronic pain during the COVID-19 pandemic in Sergipe and Brazil. To identify beliefs and expectations of fibromyalgia patients regarding physiotherapy through tele-rehabilitation. To investigate the feasibility and acceptability of synchronous and asynchronous tele-rehabilitation exercises and pain education for patients with FM. Methods: The present research involved observational studies, cross- sectional analysis, and a randomized feasibility study with qualitative and quantitative analyses. The survey on the impact of the pandemic on chronic pain was conducted using a questionnaire attached to the Google Drive Forms application, consisting of objective and clear questions about pain characteristics, psychoemotional factors, sleep quality, and level of physical activity. For the feasibility study, 24 women with FM were randomized, with 12 participants engaging in 8 weeks of multimodal exercises through video conferencing (synchronous), while the other 12 received prerecorded videos of the same exercises (asynchronous). Both groups received pain education. Feasibility was assessed by exercise adherence (total days), participation frequency (patients per week), exercise attendance (times per week), and dropout rates. Pain intensity and fatigue were evaluated using an 11-point numerical rating scale. The Tampa Scale of Kinesiophobia and Exercise Adherence Scale were used. To assess the perception, acceptability, and reasons for adherence to tele-rehabilitation exercises among FM patients, individual semi-structured interviews were conducted via video conferencing before and after the protocol. The interviews were recorded with consent and transcribed using MAXQDA® software. An inductive approach was employed through data triangulation, in which the data were coded into categories and subcategories. Results: This research yielded five articles: two regarding the impact of the pandemic on patients with chronic pain in Sergipe and Brazil, and three focusing on feasibility, perceptions, facilitators, and barriers to tele-rehabilitation. In Sergipe, 85 individuals with FM, migraine, and low back pain responded to the pandemic impact questionnaire. Approximately 70% of the sample reported worsening pain intensity, while over half of the individuals (58.8%) reported intense anxiety. Additionally, more than half of the sample reported poor sleep quality (51.8%). Just over 60% of the sample did not engage in physical activity. Regression analysis showed that lack of physical activity had a 335% chance of increasing pain intensity (β: -1.095, OR: 0.335, p = 0.025), a 244% chance of increasing anxiety (β: -1.412, OR: 0.244, p = 0.013), and a 250% chance of causing insomnia (β: -1.353, OR: 0.250, p = 0.010). Subsequently, 973 individuals from across Brazil were evaluated, with 63.5% having fibromyalgia, and the majority being female (98.3%). Social isolation was associated with pain during daily activities (p < 0.05). Binary or multinomial logistic regression analyses showed that anxiety increased the odds ratio by 395% for individuals with chronic pain to experience pain (β: 1.375; OR: 3.956; p = 0.001), and higher pain intensity increased the odds ratio by 62.3% for these individuals to not engage in physical activity (β: -0.474; OR: 0.623; p = 0.001). Moreover, pain increased the odds ratio by 186.9% for individuals with chronic pain to have insomnia (β: 0.625; OR: 1.869; p = 0.001), as did anxiety, which increased the odds ratio by 182.9% (β: 0.604; OR: 1.829; p = 0.001). Pain intensity increased the odds ratio by 160.4% for individuals with chronic pain to take sleep medications (β: 0.472; OR: 1.604; p = 0.001). Based on the 30 qualitative reports conducted prior to tele-rehabilitation, the interviewed participants expected to benefit from home therapy due to flexible scheduling, elimination of travel, socialization, and lower risk of contamination. In the analyses following tele-rehabilitation, 24 patients mentioned identification with other FM patients, group exercises, synchronous therapist supervision, and flexible scheduling as facilitators of tele-rehabilitation. Barriers included difficulty in coping with pain and fatigue, lack of motivation, lack of supervision, and limiting beliefs. Regarding feasibility results, there was a dropout rate of 7/12 (58.3%) in the synchronous group and 10/12 (83.3%) in the asynchronous group. In the synchronous group, the average exercise days were 13.87 ± 6.01 (95% CI: 7.86 to 19.88), while in the asynchronous group, it was 5.12 ± 5.11 (95% CI: 0.01 to 10.23). Participants exhibited higher average pain and fatigue levels in the initial weeks of exercises, with a gradual reduction until the 8th week. They demonstrated low exercise adherence behavior and high kinesiophobia. Qualitative analysis revealed reasons for adherence such as sense of belonging among patients, therapist supervision, and perception of pain and functionality improvement. Reasons for non-adherence included pain and fatigue, difficulty accessing technology, and lack of therapist supervision. Conclusion: The pandemic has exacerbated the vicious cycle between painful symptoms, psychoemotional aspects, and sleep disturbances in patients with chronic pain in Sergipe and Brazil. Furthermore, we observed an intensification of these factors associated with reduced levels of physical activity. Identification in group activities among FM patients and therapist supervision should be considered as important facilitators for tele-rehabilitation. However, difficulty in coping with pain, lack of motivation, and limiting beliefs serve as barriers. Asynchronous tele-rehabilitation appears to be non-feasible for the treatment of individuals with FM due to low adherence to the exercise program. The synchronous modality appears to generate greater acceptability due to therapist supervision and group exercises for fibromyalgia patients.